Comics-reading among the upper primary school children of the Division of City Schools in Manila and its implications to curriculum and instruction - Guerrero, Carolina S. 1948- (1975)
This is an investigation of the extent of comics-reading among the upper primary school children in the Division of City Schools in Manila and its implications on curriculum and instruction.
Thesis (M.Ed.)--University of the Philippines
Keywords: Comic books, strips, etc; Education, Elementary